Faulkner: A Biography. By Joseph Blotner. New York: Random House, 1974. - Eileen Klink (Ilha do Desterro)
Until the publication of The Sound and the Fury, October 7, 1929, William Faulkner knew more rejection than acceptance. Sartoris, published early the same year, had received mixed reviews, and Faulkner was "disappointed and discouraged by its reception" (Blotner: 236). However, The Sound and the Fury granted him his first taste of critical acclaim and international fame; he was heralded as a new Euripides, and his book was compared with Greek tragedy.